Deixis Analysis of Ed Sheeran’s Speech “Embrace Your Weirdness” - Pyarka, Rediva Afsana; Mauriyat, Arham (IKIP Siliwangi, 2025)
This article aims to identify deixis found in the speech of Ed Sheeran “Embrace Your Weirdness” particularly to analyze the most dominant used deixis. This research used a qualitative method with data collected from the English Speech video of Ed Sheeran’s “Embrace Your Weirdness”. The analysis analysis found 128 that, according to the five types of deixis, consist of 102 personal words, five spatial words, 10 temporal words, 10 discourse words, and one social word. The most dominant deixis was Personal Deixis with 80%. The most dominant deixis was personal deixis with 80%. it can be concluded the most dominant words used in speech was personal deixis related to the personal deixis as represented of the speaker as the main person of their speech dialog. The result will be depends on speech context it proved from the use of first person singular and plural such as “I” for the person and “we” or “our” to represent an agency or organization.